The irredeemable? How men convicted of sexual offenses reflect and reconcile redemption and condemnation scripts on the path to desistance - Kras, Kimberly Raye (Deviant behavior, 2022)
Desistance from sexual offending is of great import to scholars, practitioners, and the public. Despite theoretical advances in life course theories generally, the same work is only beginning for subgroups, like individuals convicted of sexual offenses, who may have a different desistance process than other types of offense categories due to the nature of the crime, structural disadvantage, and mandated treatment contexts. The current study considers the applicability of narrative identity theory, particularly the expression of condemnation and redemption scripts, among a sample of men convicted of sexual offenses. Using narrative analysis of in-depth interviews from a longitudinal qualitative dataset, cognitive scripts emerged in ways that uniquely apply to sex offending behavior and the experience of being labeled a ‘sex offender.’ Participants uniformly express condemnation scripts related to the labeling and structural experience of constant supervision by an array of entities, but seek and find redemption through the experiences offered in treatment. Findings from this study contribute to the growing literature on desistance from sexual offending and have implications for new theoretical developments within life course criminology.